Determinants Factor of The Use Of E-Wallets for Students and According to The Islamic Perspective - Deby Alicia Zurly; Dimas Bagus Wiranatakusuma; Alvaizy Dwi Putra Paputungan (Proceedings International Conference on Sustainable Innovation (ICoSI), 2023)
One of the best inventions of the 21st century is the electronic wallet (e-wallet) which is an integral part of the electronic payment system. As of today, almost all citizens in Indonesia use e-wallets as a payment method. E-wallet is an application or feature developed to make it easier for users to make payments. The use of e-wallets can be accessed easily via the internet, can have a positive impact and also have a negative impact on the use of electronic money services.The study involved students consisting of a man, as well as a woman with ages varying from 19 to 24 years old. Using a qualitative approach, this study uses in-depth interviews as a data collection technique and also obtains from relevant websites or journals. This research shows that E-wallets have grown very rapidly and are used by various groups, including students as millennials. E-wallets are not only understood as a place to store money electronically, but also as a digital payment system with various features, such as top ups, bill payments, bank card storage, money transfers and withdrawals, etc. Students use e-wallets for various purposes, such as paying for online transportation, buying food/drinks, paying bills, etc. There are several fundamental reasons students use e-wallets as a payment method because of the promos offered, ease of transactions, and ease of operation. . In using e[1]wallets, students not only feel comfortable in shopping, but also the convenience of paying because it can be done anywhere as long as the user is connected to the internet. Various conveniences offered by e-wallets, one of which is the simple appearance of the application that allows many users to understand how to operate it quickly